(untitled) (Revista Crioula, 2020)
This work work aims to compare the compositional form of the song, “Perisséia” by Tom Zé to that of Macunaíma: the hero without any character, by Mário de Andrade. As we expected to demonstrate, the bahian musician's song establishes a creative homology with the formal principles from the modernist writer's book